Prophylactic Incisional Negative Pressure Wound Therapy Reduces the Risk of Surgical Site Infection After Caesarean Section in Obese Women: A Pragmatic Randomized Clinical Trial. Issue 1 (March 2020) - Hyldig, N.; Vinter, C.A.; Kruse, M.; Mogensen, O.; Bille, C.; Sorensen, J.A.; Lamont, R.F.; Wu, C.; Heidemann, L.N.; Ibsen, M.H.; Laursen, J.B.; Ovesen, P.G.; et al.
Abstract : ( BJOG . 2019;126:628–625) About 10% of obese patients experience surgical site infection after cesarean delivery, despite recognized interventions such as prophylactic antibiotics and antiseptic skin preparation to help reduce this maternal risk. An alternative to the standard postoperative dressing (SPD) that has been shown to reduce the risk of surgical site infections in nonobstetric patients is incisional negative pressure wound therapy (iNPWT). There are only a few studies that have focused on this intervention in obstetric patients undergoing cesarean delivery. This study aimed to assess the effectiveness of prophylactic iNPWT on obese patients after cesarean delivery.